Train to Pakistan
Train To Pakistan is a historical novel by Khushwant Singh, published in 1956. It recounts the Partition of India in August 1947.Instead of depicting the Partition in terms of only the political events surrounding it, Singh digs into a deep local focus, providing a human dimension which brings to the event a sense of reality, horror, and believability.It is the summer of 1947. But Partition does not mean much to the Sikhs and Muslims of Mano Majra, a village on the border of India and Pakistan. Then, a local money-lender is murdered, and suspicion falls upon Juggut Singh, the village gangster who is in love with a Muslim girl. When a train arrives, carrying the bodies of dead Sikhs, the village is transformed into a battlefield, and neither the magistrate nor the police are able to stem the rising tide of violence. Amidst conflicting loyalties, it is left to Juggut Singh to redeem himself and reclaim peace for his village.
Keywords: Political violence -Fiction. India -History -Partition, 1947 -Fiction. Pakistan -Fiction.